2001
DOI: 10.1161/hc5001.100795
|View full text |Cite
|
Sign up to set email alerts
|

Low Hepatic Lipase Activity Is a Novel Risk Factor for Coronary Artery Disease

Abstract: Background-The crucial function of hepatic lipase (HL) in lipid metabolism has been well established, but the relationship between HL activity and coronary artery disease (CAD) is disputed. Methods and Results-We measured HL activity in the postheparin plasma of 200 consecutive men undergoing elective coronary angiography and determined the degree of CAD with the extent score, which has been shown to be better correlated with known risk factors than other measures of CAD extent. We found a significant inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…Numerous reports indicate that HL can have either pro-atherogenic or anti-atherogenic activities in humans and mice, depending on the details of the system undergoing study. 30,31,32 For example, alterations in HL expression result in strikingly different effects in apoE KO and LDLR KO mice, despite the similarities in morphology of their aortic atherosclerotic lesions. HL deficiency dramatically reduces aortic root atherosclerosis in apoE knockout mice 19 via poorly understood mechanisms that likely include alterations in lipoprotein metabolism, indicating a pro-atherogenic role for HL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous reports indicate that HL can have either pro-atherogenic or anti-atherogenic activities in humans and mice, depending on the details of the system undergoing study. 30,31,32 For example, alterations in HL expression result in strikingly different effects in apoE KO and LDLR KO mice, despite the similarities in morphology of their aortic atherosclerotic lesions. HL deficiency dramatically reduces aortic root atherosclerosis in apoE knockout mice 19 via poorly understood mechanisms that likely include alterations in lipoprotein metabolism, indicating a pro-atherogenic role for HL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of HL on murine atherosclerosis of this sort has not be defined previously; however, examination of HL effects on coronary arterial atherosclerosis in humans has been reported. 30 The diverse effects of HL on atherosclerosis in different systems is not surprising, because HL is a complex protein that exhibits distinct lipolytic 16 and ligand-binding 13-15,38 -41 activities that have multiple effects on lipoprotein composition and metabolism, and thus could influence atherogenesis via a variety of mechanisms. 29,33 For example, in apoE KO mice, HL deficiency may be anti-atherogenic because it raises HDL cholesterol, increases the capacity of HDL to promote cellular cholesterol efflux in vitro, 19 prevents HL-mediated increases in the atherogenicity of very-low-density lipoprotein particles, 19,34,35 increases plasma apoA-I and apoA-IV levels, 19,20 or alters the phospholipid composition of lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, human and animal studies support both proatherogenic and anti-atherogenic roles for HL (14,(31)(32)(33). In humans, low or absent HL activity has been associated with increased risk of coronary artery disease (31,34,35). Other studies have concluded that decreased HL activity does not influence susceptibility to coronary artery disease (8).…”
mentioning
confidence: 99%